Current pharmacotherapeutic options for primary dyslipidemia in adults. (3rd July 2019) - Cicero, Arrigo F.G.; Landolfo, Matteo; Ventura, Fulvio; Borghi, Claudio
ABSTRACT: Introduction : Atherosclerotic cardiovascular disease (ASCVD) and its clinical manifestations, remain a leading cause of death and disability worldwide. One of the major risk factors of ASCVD is dyslipidemia and all the available guidelines suggest the importance of strategies for lipid control in a remarkable proportion of the general population. Areas covered : This review focuses on the therapeutic options available for the management of lipid disorders in adults. Expert opinion : A large body of evidence supports that statins are still the first-line option for the management of hypercholesterolemia in a large percentage of patients. Statins should be given at the appropriate dose and considering the differences in lipid-lowering potency across the different medications. The main current challenge in the treatment of lipid disorders is the need of improving patient adherence and persistence to lipid-lowering treatments beyond the drug choice and the target lipid component. To achieve this goal, the best strategy would be to treat the patients by using the appropriate drugs given at adequate doses to reach the treatment target. We should also avoid drug interactions, monitor possible untoward side effects and promote adherence to treatment by tailoring treatment strategies to each patient.